Binding of de novo synthesized radiolabeled juvenile hormone (JH III) by JH receptors from the Cuban subterranean termite Prorhinotermes simplex and the German cockroach Blattella germanica. (December 2021) - Milacek, Matej; Bittova, Lenka; Tumova, Sarka; Luksan, Ondrej; Hanus, Robert; Kyjakova, Pavlina; Machara, Ales; Marek, Ales; Jindra, Marek
Abstract: Juvenile hormone (JH) controls insect reproduction and development through an intracellular receptor complex comprising two bHLH-PAS proteins, the JH-binding Methoprene-tolerant (Met) and its partner Taiman (Tai). Many hemimetabolous insects including cockroaches strictly depend on JH for stimulation of vitellogenesis. In termites, the eusocial hemimetabolans, JH also regulates the development of caste polyphenism. Studies addressing the agonist ligand binding to recombinant JH receptors currently include three species belonging to two holometabolous insect orders, but none that would represent any of the hemimetabolous orders. Here, we examined JH receptors in two representatives of Blattodea, the cockroach Blattella germanica and the termite Prorhinotermes simplex . To test the JH-binding capacity of Met proteins from these species, we performed chemical synthesis and tritium labeling of the natural blattodean JH homolog, JH III. Our improved protocol increased the yield and specific activity of [10- 3 H]JH III relative to formerly available preparations. Met proteins from both species specifically bound [ 3 H]JH III with high affinity, whereas Met variants mutated at a critical position within the ligand-binding domain were incapable of such binding. Furthermore, JH III and the synthetic JH mimic fenoxycarb stimulated dimerization between Met and Tai components of the respective JH receptors of both species. These data present primary evidence for agonist binding by JH receptors in any hemimetabolous species and provide a molecular basis for JH action in cockroaches and termites. Graphical abstract: Image 1 Highlights: Efficient de novo chemical synthesis yields [ 3 H]JH III of high specific activity. Met and tai JH receptor genes are well conserved between a cockroach and a termite (Blattodea). JH receptor agonists induce interaction between blattodean Met and Tai proteins. Met proteins from both blattodean species bind synthetic [ 3 H]JH III with high affinity. Newly synthesized [ 3 H]JH III is an important tool to study JH signaling.